Direito como fundação e constituição como promessa: um diálogo com Hannah Arendt - Tayara Talita Lemos (2012)
From the work of Hannah Arendt, we will discuss the fact that Law has had its legitimacy mitigated since modernity. This is due to the so-called loss or forgetfulness of politics. Since then, the shattering of the Roman triad tradition, authority and religion carries the problem that the new standards of the modern world can not legitimize the power and the law. The consumer relations then given demonstrate the phenomenon of the transformations tendency of political man into animal laborans, a man that produces and consumes, in all (or almost all) of his public activities. The movement described by the author requires the construction of a new public-political space which is the in-between, suitable for concerted action (action in concert) among men. In this diversity, it is possible to reframe Politics in order to reestablish the instances of power and repair the loss of authority. Also through these foundations, the Constitution can be used as a means of rooting foundations created by Law.